PENGARUH BUDAYA ORGANISASI, GAYA KEPEMIMPINAN DAN KOMPETENSI TERHADAP KINERJA KARYAWAN PD.BPR BKK BATANG - Ummi Afifa Widyaningsih, 15.05.52.0294; Suhana, Suhana (Students' Journal of Accounting and Banking, 2019)
This study aims to analyze the influence of organizational culture, leadership style, and competence on employee performance in PD. BPR BKK Batang. The independent variables in this study are organizational culture, leadership style, and competence and the dependent variable used in this study is employee performance. This study uses a questionnaire as a data collection tool. Data analysis in this study using multiple linear regression analysis, it is known that: (1) organizational culture has a positive and significant effect on employee performance. (2) leardership style has a positive and significant effect on employee performance. (3) competence has a positive and significant effect on employee performance in PD. BPR BKK Batang.